On the stress relaxation mechanism of GaN thin films grown on Si(111) substrates. (December 2019) - Koryakin, A A; Mizerov, A M; Bouravleuv, A D
Abstract: Gallium nitride (GaN) thin films grown on Si(111) substrates via plasma-assisted molecular beam epitaxy were investigated. The morphology of GaN films was studied by scanning electron microscopy. It was found that GaN films at nanoscale contain a large amount of cavities. The Raman measurements of GaN/Si(111) system were performed and showed that the position of the GaN E2 (TO) band is close to that of unstrained GaN. We proposed a stress relaxation mechanism to explain the low stress state of GaN films.